Вплив тимчасової гіпотермії на стан морфологічних показників імунних органів однорічок сріблястого карася (Carassius gibelio) - Присяжнюк, Н. М.; Prysiazhniuk, N. M.; Горчанок, Анна Володимирівна; Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; Носенко, М. М.; Nosenko, M. M. (Дніпровський ДАЕУ, 2021)
Досліджено вплив тимчасової гіпотермії на стан морфологічних показників імунних органів однорічок сріблястого карася. Встановлено, що гіпотермія сприяє виникненню тенденції до зменшення основних показників органометрії вторинних імунних органів сріблястого карася. Вплив гіпотермії має прояв у збільшенні рівня варіабельності основних показників органометрії імунних органів сріблястого карася. The influence of temporary hypothermia on the state of morphological parameters of the immune organs of Carassius gibelio was studied. It is established that hypothermia contributes to the tendency to decrease the main indicators of organometry of secondary immune organs of Carassius gibelio. The effect of hypothermia is manifested in an increase in the level of variability of the main indicators of the organometry of the immune organs of Carassius gibelio.
Effect of temporary hypothermia on the state of morphological indicators of immune organs one year Carassius gibelio
Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477
Keywords: гіпотермія; hypothermia; нирки; kidneys; печінка; liver; селезінка; spleen; індекс органу; organ index; маса; weight; об’єм; volume; сріблястий карась; Carassius gibelio